ANALISIS DETERMINAN BELANJA DAERAH PADA KABUPATEN/KOTA DI PROVINSI JAWA TIMUR - Hapsari Nur Aziza (2020)
This study aims to test the effect of Local Own-Source Revenue, General Allocation Fund, Special Allocation Fund, and Population Amount towards Local Expenditure. This study used all 39 districts/cities in the East Java Province as samples. The sample collection method used in this study is the saturated sample method. This study uses secondary data from the Budget Realization Report and population. The analysis method used is the double linear regression method using SPSS with a significance rate of 5% (0.05). The result of this study shows that Local Own-Source Revenue, General Allocation Fund, and Population Amount has a significant effect towards Local Expenditure. Meanwhile the Special Allocation Fund partially does not have a significant effect towards Local Expenditure.